Dividend policy, share price and return: a study on the Johannesburg Stock Exchange - Sealy, N R (College of Accounting, 2016)
This thesis consists of an empirical investigation into the effects of firms' dividend policies on the prices of and returns realised on their ordinary shares listed on the Johannesburg Stock Exchange. A review of published theories as to whether the dividend policy of a firm ought to affect its value revealed that, under conditions approximating perfect capital markets, no dividend influence should be expected. Because of the wide range of market imperfections and their non uniform effect in the preferences they create amongst shareholders no consensus as to their aggregate influence on security returns exists. The writer's review of studies conducted by other researchers on overseas markets indicated no dividend effect. The main empirical investigation conducted by the writer into the effects of dividend policy on the value of a firm made use of cross sectional regression techniques and an expanded ex post form of the capital asset pricing model. The results of this test indicated a negative dividend preference by investors which is more likely to have resulted from the heavier taxation of dividends than capital gains, than from a dividend aversion in a perfect capital markets situation. The implication of these findings is that investors experiencing heavier taxation on dividend income than on capital gains may generally ignore the dividend policies of prospective investees, while all other investors stand to gain by biasing their investment selection toward high pay-out shares. In favouring certain pay-out ratios adequate regard must, however, be given to maintaining an adequately diversified portfolio. The test results further imply that firms may increase their value by reducing the dividend pay-out and accordingly, with capital requirements met from internal sources, reducing the amount of new capital raised through equity issues.